1976
DOI: 10.1128/jb.127.2.855-862.1976
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipoteichoic acid of Streptococcus pyogenes and its stabilized L-form and the effect of two antibiotics upon its cellular content

Abstract: Membrane lipoteichoic acid continues to be synthesized by an osmotically fragile, stabilized L-form of Streptococcus pyogenes. Chromatographic and electrophoretic comparisons indicate that the lipid componenent of lipoteichoic acid in this L-form and its parental streptococcus is glycerophosphoryldiglucosyl diglyceride and not phosphatidylkojibiosyl diglyceride. Based upon dry weight determinations, the yield of lipoteichoic acid from the L-form is 0.19%, as compared with 0.97% from the streptococcus. When gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
(47 reference statements)
3
23
0
Order By: Relevance
“…Does not take into account LTA absorbed to protoplasts or membranes because only the supernate of these samples was analyzed. (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Does not take into account LTA absorbed to protoplasts or membranes because only the supernate of these samples was analyzed. (19).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid moiety of group A streptococcal LTA has been determined to be glycerophosphoryldiglucosyl diglyceride ( Fig. 3) (19). The presence of fatty acids on LTA and absence of fatty acids on dLTA was confirmed by gas-liquid chromatography.…”
Section: Characterization Of the Cleavage Site(s) Within The Lta Molementioning
confidence: 93%
“…Therefore, L-form cytotoxicity appears to be equally as effective for cultured mouse glomeruli and human cell monolayers. Bar, 1 1>m. an earlier study that had documented the lack of any apparent difference in the destructive ability of the LTA isolated from either the L-form or its parental S. pyogenes for human kidney monolayers in tissue culture despite differences in the length and composition of this amphiphile from these two organisms (13,14). Finally, and as opposed to an earlier study with cultured human cell monolayers (1), glomerular destruction did not increase when the concentration of LTA was increased.…”
Section: Discussionmentioning
confidence: 63%
“…LTA. LTA was obtained from S. pyogenes type 12 as detailed previously (14) and stored at -70°C in the dry state with a desiccant. A stock solution of LTA in TCM without serum, adjusted to pH 7.2 with 5.6% sodium bicarbonate, was used to dispense the appropriate amount(s) of this amphiphile as needed for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The polyglycerol phosphate backbone is substituted to various degrees with glycosyl, alanyl, and acyl residues (for reviews, see references 10 and 15). The lipid moiety of group A streptococcal LTA is glycerophosphoryldiglucosyl diglyceride (14). Streptococcal LTA binds to a variety of cell membranes (3)(4)(5)(6)11), and the necessity of ester-linked fatty acids for LTA membrane binding activity was demonstrated by experiments which showed that: (i) the cleavage of ester-linked fatty acids by mild alkaline hydrolysis resulted in the loss of binding activity (5,11) and (ii) the cleaved lipid fraction of LTA inhibited the binding of the intact molecule (2).…”
mentioning
confidence: 99%